An efficient method exploiting the waste heat from a direct carbon fuel cell by means of a thermophotovoltaic cell. (1st October 2017) - Yang, Zhimin; Peng, Wanli; Liao, Tianjun; Zhao, Yingru; Lin, Guoxing; Chen, Jincan
Graphical abstract: Highlights: A new direct carbon fuel cell-thermophotovoltaic cell hybrid system is established. The waste heat from a direct carbon fuel cell can be efficiently exploited. The maximum power output density of the hybrid system is calculated. Lower and upper bounds of optimized parameters are determined. Performances of several direct carbon fuel cell-based hybrid systems are compared. Abstract: Based on the current models of the direct carbon fuel cell and thermophotovoltaic cell, a new hybrid system is proposed to efficiently exploit the waste heat from a direct carbon fuel cell by terms of a thermophotovoltaic cell. The expressions of the power output and the efficiency of the hybrid system are analytically derived and the maximum power output density is numerically calculated. It is found that under some given conditions, the maximum power output density of the hybrid system can attain 734.7 W m −2, which is more than 2 times of that of a single direct carbon fuel cell. Moreover, the optimal region of the hybrid system is determined through the introduction of a new objective function (i.e., the product of the efficiency and the power output). The selective criteria of some key parameters such as the power output density, efficiency, current density of the direct carbon fuel cell, and area ratio of the direct carbon fuel cell to the thermophotovoltaic cell are provided. The effects of the carbon particle slabs in the packed bed anode of the fuel cell on some key parameters are discussed. The maximum power output density of the hybrid system under the differently operating temperatures of the direct carbon fuel cell are calculated and compared with those of other direct carbon fuel cell-based hybrid systems. The results of this study indicate that the thermophotovoltaic cell can efficiently harvest the waste heat produced in the direct carbon fuel cell and the direct carbon fuel cell-thermophotovoltaic cell hybrid system have some obvious advantages over other direct carbon fuel cell-based hybrid systems.